Change and Continuity: Adaption of Persons Working in the Secondary Sector During the Period of Socio-Economic Reforms in the 1990s in Estonia - Kazjulja, Margarita; Saar, Ellu (Studies of Transition States and Societies, 2010)
The aim of this paper is to analyse the interrelationship between the structural changes and personal destinies of people who worked in the secondary sector at the beginning of the transition period. The focal question is whether structural and institutional changes were brought about by a minimum of adaptations and fluctuations or a by maximum of turbulence and mobility. The paper is based on indepth interviews conducted in 2003 and 2004 with people who graduated from secondary educational institutions in 1983 and belong to the so-called ‘winners’ cohort. One of the pivotal results of the analysis is that when companies were winding down and being reorganised, it launched processes of intercompany workers’ displacement and lead to their imminent unemployment. Individuals changed their plans and behaviour because they had to adapt. Opportunities proved to be less a matter of individual control and planning, than of unfavourable structural conditions. A work place in the secondary sector often worked as a ‘push’ factor for mobility during the reforms, as massive layoffs and restructuring in the economy did not leave any other choices for people than to start looking for new possibilities. In spite of some attempts to set up businesses, the majority of former industrial workers belong to the same occupational group and are working in the same sector, even 15 years after the reforms. This means that the relative occupational ranking of the workers remained the same despite the change in the political and social order.